Proteomic and biomarker studies and neurological complications of pediatric sickle cell disease. Issue 11 (6th November 2014) - Lance, Eboni I.; Casella, James F.; Everett, Allen D.; Barron‐Casella, Emily; Everett, Allen; Ignjatovic, Vera
<x xml:space="preserve">Abstract</x> Biomarker analysis and proteomic discovery in pediatric sickle cell disease has the potential to lead to important discoveries and improve care. The aim of this review article is to describe proteomic and biomarker articles involving neurological and developmental complications in this population. A systematic review was conducted to identify relevant research publications. Articles were selected for children under the age of 21 years with the most common subtypes of sickle cell disease. Included articles focused on growth factors (platelet‐derived growth factor), intra and extracellular brain proteins (glial fibrillary acidic protein, brain‐derived neurotrophic factor), and inflammatory and coagulation markers (interleukin‐1β, l‐selectin, thrombospondin‐1, erythrocyte, and platelet‐derived microparticles). Positive findings include increases in plasma brain‐derived neurotrophic factor and platelet‐derived growth factor with elevated transcranial Dopplers velocities, increases in platelet‐derived growth factor isoform AA with overt stroke, and increases in glial fibrillary acidic protein with acute brain injury. These promising potential neuro‐biomarkers provide insight into pathophysiologic processes and clinical events, but their clinical utility is yet to be established. Additional proteomics research is needed, including broad‐based proteomic discovery of plasma constituents and blood cell proteins, as well as urine and cerebrospinal fluid components, before, during and after neurological and developmental complications.